Resource Scarcity and Antisocial Behavior - Prediger, Sebastian; Vollan, Björn; Herrmann, Benedikt (Journal of Public Economics, 2014)
This paper examines whether exposure to persistent resource scarcity on the commons affects pastoralists' readiness to engage in antisocial behavior towards their fellow commons users. The region under study is divided into two areas according to exogenous variations in biomass production stemming from geological peculiarities. We conducted a joy-of-destruction game with pastoralists from both areas and provide evidence for a positive relationship between antisocial behavior and long-term exposure to scarcity. Antisocial behavior among villagers occurs twice as often in an area where resources are scarcer and competitive pressure is higher. Our results remain robust to the inclusion of various controls, including beliefs, socio-demographics, absolute and relative income, and within-group inequality. If one interprets decreasing another participant's payoff below one's own as a tendency towards conflict behavior, our results suggest a higher risk of conflict among resource users in areas of greater scarcity.